Pemberdayaan Masyarakat di Desa Kalikurmo Berbasis Kearifan Lokal: Pelatihan e-Commerce untuk Meningkatkan Akses Pemasaran dan Penjualan Produk Hasil Desa - Cucun Alep Riyanto; I Gede Kesha Aditya Kameswara; Afif Afina; Ira Tyas Kurniasari; Yemima Kristiani (Universitas Kristen Satya Wacana Salatiga, 2021)
The community service activities are very crucial to be done in order to improve human resources in Kalikurmo village as well as helping people in this village to improve their income. The aim of this activities is to train the community in Kalikurmo village, especially Gedad hamlet, with basic knowledge about e-commerce and its use. The method used is data collection through questionnaires, counseling, e-commerce training and photo techniques. The results obtained from this community service activity are that this activity improves the quality of students themselves, and e-commerce training for the community is proven to be used by the community to promote and sell their product or handicrafts.